Implementasi Buku Sumang Opat Majelis Adat Aceh dalam Upaya Pencegahan Kenakalan Remaja di Kabupaten Bener Meriah - Erna Fitriani Hamda; Fitrianti; Elvianda (Program Studi Pendidikan Agama Islam, 2025)
Currently, many teenagers rarely follow the rules of the Quran and Hadith. They often neglect gadgets and play games. Many teenagers have also started dating, forgetting the sin of excessive dating. Their behavior and actions often go beyond Islamic law and the laws in Indonesia, particularly in Aceh. Many teenagers engage in premarital sex, premarital pregnancy, drug use, brawls, and even murder of their teachers or those around them. Adolescence is a time of intense attention seeking, especially from those closest to you. This attention requires guidance and direction from the right people to prevent undesirable outcomes. The Acehnese traditional council's role in this regard is crucial, including the implementation of the Sumang Opat book to prevent juvenile delinquency in Bener Meriah Regency. This study used a qualitative method with a descriptive approach. This study aims to determine the implementation of the Sumang Opat book by the Acehnese traditional council in preventing juvenile delinquency in Bener Meriah Regency. The results of this study indicate that the implementation carried out by the Acehnese traditional council in Bener Meriah Regency using the Sumang Opat book in preventing juvenile delinquency has been quite good through various activities such as outreach among the community, schools and conducting seminars or becoming a director in a training or FGD.